Learning Through Examining the Tourist Experience - Shaik Hussain, S. A. (International Journal of Education and Research, 2013)
In the field of travel and tourism, scholars with interest in consumer behaviour studies have explored different variables and linked them with individual tourist behaviour. Variables such as destination image, environmental awareness, service perception, preferences, and motivations for travel are commonly used to understand and predict destination selections and travel behaviour.This study is intended to shed some further light on this issue and contribute to knowledge in this area. A survey that gained a total of 1340 respondents was carried out in three destinations in Sarawak between 2006 and 2008 to gain an understanding of their behaviours travelling into Sarawak. Regional tourism organizations can also play an important role in destination marketing and tourism product development and to recommend appropriate marketing strategies that could be adopted by tourist organizations based on a further understanding of travel behaviour. As shown from the analysis, Sarawak tourism market is not big enough to have very many segments; therefore the different regions need to have common and coordinated marketing strategies in order to gain market share.